Militarized Masculinities: Gender Norms, Women and LGBTIQ+ in European Armed Forces - Ignatčikas, Arnoldas (Sociologija. Mintis ir veiksmas, 2024)
This article examines the construction of militarized masculinities within the European Union. It aims to identify the qualities deemed necessary for a militarized masculine man in this context. The analysis focuses on three dimensions: the normative image of militarized masculinity, the position of women in the military, and the integration of LGBTIQ+ individuals, particularly homosexual and transsexual persons. The findings suggest that women are often positioned as complementary to men, thereby reinforcing traditional gender hierarchies. Homosexual men may be accepted, but typically only if they conform to dominant masculine norms. Drawing on Judith Butler’s theory of gender performativity, the article argues that militarized masculinity is not inherent but socially constructed. Jasbir Puar’s concept of homonationalism is used to demonstrate how selective aspects of homosexual identities are incorporated into military structures in Lithuania, Greece, Germany, and the Netherlands. The empirical component is based on semi-structured interviews with eight military professionals, revealing prevailing gender norms, behavioral expectations, and the conditional inclusion of sexual minorities within military institutions. The article concludes that rethinking the military beyond a narrowly defined masculine ideal is essential for promoting greater inclusivity and challenging dominant gender norms.
Keywords: gender; gender norms; masculinity; military; NATO; LGBTIQ+